2020
DOI: 10.2217/fon-2020-1003
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns, Healthcare Use and Costs in Triple-Class Exposed Relapsed and Refractory Multiple Myeloma Patients in the USA

Abstract: Aim: To estimate treatment patterns and healthcare costs among triple-class exposed relapsed and refractory multiple myeloma (RRMM) patients. Materials & methods: Eligible patients had ≥1 line of therapy (LOT) each of proteasome inhibitors, immunomodulatory drugs and daratumumab in December 2015–September 2018 and received a new LOT. Results: A total of 154 patients were included with a median follow-up of 6.2 months. Median time from diagnosis to new LOT was 41.0 months. Kaplan–Meier estimate of median ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…In this study, daratumumab was used both in monotherapy and in combination with a variety of different agents. This is consistent with other reports of how daratumumab is used in the real world [ 23 ]. While a majority of patients initiated daratumumab in third line or after, the proportion of patients initiating daratumumab in earlier lines increased in the subset of patients initiating in 2018 or later.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, daratumumab was used both in monotherapy and in combination with a variety of different agents. This is consistent with other reports of how daratumumab is used in the real world [ 23 ]. While a majority of patients initiated daratumumab in third line or after, the proportion of patients initiating daratumumab in earlier lines increased in the subset of patients initiating in 2018 or later.…”
Section: Discussionsupporting
confidence: 93%
“…Our study findings reflect more recent cost estimates (through February 2021) and are generally consistent with those reported in the study by Madduri et al in which patients were also identified from the MarketScan CCAE and MDCR databases. In that study, 154 MM patients were selected who had TCE and initiated at least one subsequent LOT between December 1, 2015 and September 30, 2018 [ 8 ]. Total all-cause healthcare costs were estimated at $37,033 PPPM in the 6 months (median follow-up) after initiation of another LOT post-TCE; MM-related healthcare costs represented 96% of total all-cause healthcare costs [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 The treatment regimens selected by hematologists in our survey across Europe and Canada are consistent with regimens from the published US studies. Madduri et al 15 found that an immunomodulatory drug alone (11.0%) or in combination with daratumumab (18.2%) or a PI (15.6%) were the most used regimens in the first line of therapy after TCE. 15 Mehra et al 13 similarly reported elotuzumab-, pomalidomide-, and carfilzomib-based regimens to be used most frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Madduri et al 15 found that an immunomodulatory drug alone (11.0%) or in combination with daratumumab (18.2%) or a PI (15.6%) were the most used regimens in the first line of therapy after TCE. 15 Mehra et al 13 similarly reported elotuzumab-, pomalidomide-, and carfilzomib-based regimens to be used most frequently. The global KarMMa-RW study 14 likewise reported a variety of treatments, with 94 unique regimens used for the next-line treatment of 190 TCE patients; common combination regimens consisted of carfil-zomib, pomalidomide, daratumumab, lenalidomide, or elotuzumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation